Papillary Ependymoma WHO Grade II of the Aqueduct Treated by Endoscopic Tumor Resection - Andreas M. Stark; Heinz-Herrmann Hugo; Arya Nabavi; H. Maximilian Mehdorn (Case Reports in Medicine)
Papillary ependymoma is a rare tumor that may be located along the ventricular walls or within the spinal cord. We report the case of a 54-year-old patient with a papillary ependymoma WHO grade II arising at the entrance of the aqueduct. The tumor caused hydrocephalus. The tumor was completely removed via a right-sided endoscopic approach with restoration of the aqueduct. The free cerebrospinal fluid passage through the aqueduct was not only visualized by endoscopy but also controlled by intraoperative high-field magnetic resonance imaging. Therefore, an additional endoscopic third ventriculostomy was unneccessary.